Malignant myoepithelioma (myoepithelial carcinoma) of the breast: a detailed cytokeratin study. Issue 2 (February 1995) - Lakhani, S R; O'Hare, M J; Monaghan, P; Winehouse, J; Gazet, J C; Sloane, J P
Abstract : AIMS--To study the expression of a range of cytokeratins by malignant myoepithelioma of the breast. METHODS--Immunophenotyping was carried out using a panel of antibodies on paraffin wax embedded and frozen material using immunohistochemistry and double-labelled immunofluorescence. Electron microscopy was also performed. RESULTS--The tumour cells were positive for CAM 5.2, actin, vimentin, and cytokeratin 14 and negative for cytokeratins 18 and 19. Electron microscopy showed well formed desmosomes and hemidesmosomes together with pinocytic vesicles, plentiful rough endoplasmic reticulum and 6 nM microfilaments with focal densities. CONCLUSIONS--The pattern of cytokeratin expression provides further evidence that tumours with a specific myoepithelial phenotype occur rarely in the breast.